Nadwaga a gibkość młodzieży licealnej – raport z badań = Overweight and flexibility secondary school students – research report - Srokowska, Anna; Lewandowski, Andrzej; Kowalik, Tomasz; Piekorz, Zuzanna; Srokowski, Grzegorz; Radzimińska, Agnieszka; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Srokowska Anna, Lewandowski Andrzej, Kowalik Tomasz,Piekorz Zuzanna, Srokowski Grzegorz,Radzimińska Agnieszka, Zukow Walery. Nadwaga a gibkość młodzieży licealnej – raport z badań = Overweight and flexibility secondary school students – research report. Journal of Education, Health and Sport. 2015;5(6):482-495. ISSN 2391-8306. DOI10.5281/zenodo.30568 http://dx.doi.org/10.5281/zenodo.30568 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A482-495 https://pbn.nauka.gov.pl/works/620769 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 06.09.2015. Nadwaga a gibkość młodzieży licealnej – raport z badań Overweight and flexibility secondary school students – research report 1Anna Srokowska, 1Andrzej Lewandowski, 1Tomasz Kowalik, 2Zuzanna Piekorz, 2Grzegorz Srokowski, 2Agnieszka Radzimińska, 3Walery Zukow 1Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra i Zakład Podstaw Kultury Fizycznej, Bydgoszcz, Polska 2Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska 3Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Bydgoszcz, Polska Adres do korespondencji: mgr Anna Srokowska, Katedra i Zakład Podstaw Kultury Fizycznej UMK w Toruniu Collegium Medicum im. L. Rydygiera w Bydgoszczy ul. Świętojańska 20, 85-077 Bydgoszcz, tel. 600341155, e-mail a.srokowska@cm.umk.pl Słowa kluczowe: młodzież licealna, BMI, skłon tułowia, różnice, zależności. Streszczenie: Problem nadwagi i otyłości to temat często podejmowany przez wielu badaczy. Konsekwencje tych zaburzeń mają swoje skutki dopiero w wieku dorosłym, dlatego ważne jest wczesne wykrywanie i zapobieganie nadmiernej masie ciała. Nadwaga i otyłość może również prowadzić do obniżenia sprawności fizycznej, a co za tym idzie gibkości jako jednego z jej komponentów. Celem pracy jest ocena gibkości młodzieży licealnej o prawidłowej masie ciała i z nadwagą oraz ustalenie częstości jej występowania. Sformułowano hipotezę, że nadmierna masa ciała dotyczy populacji młodzieży licealnej, a także w negatywny sposób wpływa na poziom gibkości. Badaniami objęto 309 uczniów Liceum Ogólnokształcącego nr VIII w Bydgoszczy. Wykonano pomiary wysokości i masy ciała jako podstawowych charakterystyk, które pozwoliły na obliczenie wskaźnika wagowo-wzrostowego Queteleta (BMI). Wykonano pomiar poziomu gibkości testem skłonu tułowia w przód w pozycji siedzącej. Wykonane badania nie wykazały istotnego problemu z nadwagą i otyłością wśród uczniów klas licealnych, a także istotnego statystycznie wpływu masy ciała na gibkość badanych osób. Młodzież o podwyższonym BMI osiągnęła podobne wyniki gibkości jak uczniowie z BMI w normie. Grupa dziewcząt charakteryzowała się większymi głębokościami skłonu tułowia w przód jednakże również w tej grupie stwierdzone różnice nie były znaczące. Obliczone współczynniki korelacji poziomu gibkości z wybranymi cechami morfologicznymi wskazują na brak lub słabą zależność w grupie uczniów bez nadwagi i bardziej istotne statystycznie dodatnie oraz ujemne zależności w grupie uczniów z nadwagą. Uczniowie klas licealnych nie mają większego problemu z nadwagą, a zwiększona masa ciała nie wpływa na niższy poziom gibkości. Oznacza to, że problem skutków nadwagi w większym stopniu może dotyczyć innych cech sprawności fizycznej lub ujawniać swoje negatywne skutki w okresie dorosłości. Keywords: secondary school students, BMI, bend the trunk, differences, depending on. Abstract: The problem of overweight and obesity is a topic frequently raised by many researchers. The consequences of these disturbances have their effects until adulthood, therefore, early detection and prevention of excessive weight gain are of vital importance. Overweight and obesity can also lead to limited physical fitness, and thus flexibility as one of its components. The aim of the study is to evaluate the flexibility of school youth of normal weight and overweight and to determine the frequency of its occurrence. It was hypothesized that excessive body weight in a population of high school students has negative effects on flexibility. The study included 309 students of the High School No. VIII in Bydgoszcz. Measurements of basic morphological features (weight, height) were taken in order to determine weight-growth rate by Quetelet (BMI). Next, the level of torso flexibility in the sitting position was measured. The studies showed no significant problem of overweight and obesity among high school students, or statistically significant effect of body weight on the flexibility. Young people with a higher BMI achieved similar results in flexibility as students with a BMI in the normal range. Yet, girls were characterized by a greater suppleness than the boys. The observed differences were not significant. In turn, no correlation between the selected levels of flexibility and morphological features, was found in the students with correct weight. Statistically more significant correlations were observed in the group of overweight students. It can be concluded that students don’t suffer from obesity or overweight. Additionally, it was observed that even in students with increased weight, flexibility was not lowered. This means that the problem of the consequences of excess weight a greater extent may involve other features of physical or disclose its negative consequences in adulthood.